Lights on: Dye dequenching reveals polymersome fusion with polymer, lipid and stealth lipid vesicles - Henderson, Ian M.; Collins, Aaron M.; Quintana, Hope A.; Montaño, Gabriel A.; Martinez, Julio A.; Paxton, Walter F. (Polymer (Guilford), 2016)
Herein we develop a quantitative dye dequenching technique for the measurement of polymersome fusion, using it to characterize the salt mediated, mechanically-induced fusion of polymersomes with polymer, lipid, and so-called stealth lipid vesicles. While dye dequenching has been used to quantitatively explore liposome fusion in the past, this is the first use of dye dequenching to measure polymersome fusion of which we are aware. In addition to providing quantitative results, dye dequenching is ideal for detecting fusion in instances where DLS results would be ambiguous, such as low yield levels and size ranges outside the capabilities of DLS. The dye chosen for this study was a cyanine derivative, 1,1′-dioctadecyl-3,3,3′,3′-tetramethylindotricarbocyanine iodide (DiR), which proved to provide excellent data on the extent of polymersome fusion. Using this technique, we have shown the limited fusion capabilities of polymersome/liposome heterofusion, notably DOPC vesicles fusing with polymersomes at half the efficiency of polymersome homofusion and DPPC vesicles showing virtually no fusion. In addition to these key heterofusion experiments, we determined the broad applicability of dye dequenching in measuring kinetic rates of polymersome fusion; and showed that even at elevated temperatures or over multiple weeks' time, no polymersome fusion occurred without agitation. Stealth liposomes formed from DPPC and PEO-functionalized lipid, however, fused with polymersomes and stealth liposomes with relatively high efficiency, lending support to our hypothesis that the response of the PEO corona to salt is a key factor in the fusion process. This last finding suggests that although the conjugation of PEO to lipids increases vesicle biocompatibility and enables their longer circulation times, it also renders the vesicles subject to destabilization under high salt and shear (e.g. in the circulatory system) that may lead to, in this case, fusion. A dye dequenching assay is used to quantitatively measure the fusion of polymersomes with polymersomes, liposomes, and stealth liposomes. Although polymersome fusion with liquid-phase liposomes was quite efficient, we find that little fusion occurs with gel-phase liposomes. The efficiency is increased however, with the introduction of PEGylated lipids into the gel-phase liposomes, due to the interactions of the PEGylated lipids with the polymersome corona. [Display omitted] •The fusion of PEO-Pbd polymersomes was characterized using the dequenching of DiR, a cyanine-based fluorescent dye.•Dye-dequenching provided more quantitative information than either microscopy or light scattering.•The fusion of polymersomes with DOPC and DPPC liposomes along with stealth liposomes was investigated.•It was found that the PEO of stealth liposomes aided in the fusion process.